Business intelligence como propulsor para contibuir com a análise da evasão da EaD no ensino superior - Cunha, Juliana Tâmara Rodrigues da (Universidade Federal Rural do Semi-Árido, 2019)
Being aware of the importance and advancement of distance education courses throughout the country, our project develops a topic considered of extreme value because it is a tool with pedagogical and administrative variations in its aspects that directly aid the assertive decision making. Can be crucial to the success of the platform. Working on the importance of LEARNING ANALYTICS is a simplified way to work on the idea of managing the opportunities to organize the interaction between teacher and student and the availability of materials in various formats that aim to present the resources varied as there is a need to be seen subjectively that is, through their individuality as well as directly subsidize the faculty when it provides a range of elements that will help to evaluate their students and make better use of intellectual and management in the use of their materials.
Monografia
Keywords: Business inteligence; Evasão; Educação a Distância; Learning analytics; EAD; Technology; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA